Previsão automatizada de ondas em lagos de barragens - de Freitas Maciel, Geraldo [UNESP]; Dall'Aglio Sobrinho, Milton [UNESP]; Marcon, Caio Nilo [UNESP]; Marques, Marcelo (My University, 2006)
From a software developed by the team of the College of Engineering of Ilha Solteira FEIS/UNESP, the purpose of this work is to processing of wind velocity and fetch, in order to estimate wave height in lakes of dams produced by winds. The software, named OndisaCAD, works inside of CADs environments, AutoCAD of the Autodesk for example, thus making possible the generation of graphical results. Right now, the study of case has been made in the lake of the Hydroelectric Plant of Ilha Solteira, located in the northwest of the state of São Paulo - Brazil. The wind data are collected from meteorological stations located in the margins of the reservoir and sent by telemetry to the FEIS/UNESP.
Automated wave prediction in dam lakes